Banking Structure and Credit Growth in Central and Eastern European Countries - Aydin, Burcu (Washington, D.C. : International Monetary Fund, 2008)
Recent developments have increased questions about vulnerabilities in Central and Eastern European Countries (CEE) that are experiencing credit booms. This paper analyzes the role of foreign-owned banks in these credit booms. The results show that the CEE countries depend on foreign banks, and these foreign banks depend on interbank funding. Lending by foreign banks seems driven by economic growth and interest rate margins. This lending appears independent of economic but not financial conditions in the foreign bank's home country.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet